Residual Postoperative Valgus After Total Knee Arthroplasty for Preoperative Valgus Deformity Results in Inferior Patient-Reported Outcomes - Anastasia A. Hunt, MD; Ian Hollyer, MD; Nicole S. Pham, MPH; William J. Maloney, MD; James I. Huddleston, III, MD (Arthroplasty Today)
Background: The optimal postoperative coronal alignment after total knee arthroplasty (TKA) for preoperative valgus deformity is unknown. This study aims to evaluate the impact of postoperative coronal alignment on clinical outcomes following TKA for valgus deformities. Methods: Patients in preoperative valgus undergoing primary TKA between 2010 and 2020 with at least 1 year of follow-up were retrospectively reviewed. Preoperative and postoperative mechanical alignment was assessed on long-leg radiographs via the hip-knee-ankle angle. Postoperative alignment was categorized into valgus (>2° valgus), neutral (within 2° of the mechanical axis), or varus (>2° varus). Patient demographics, preoperative and postoperative outcome scores, and complications were collected. Results: 106 patients met inclusion criteria, with a mean preoperative valgus deformity of 11° (standard deviation ± 6.1). Postoperatively, 18 patients were in varus alignment, 58 were neutral, and 30 remained in valgus. At 2-year follow-up, multivariate analyses showed that patients in neutral or varus alignment postoperatively had superior Veterans RAND 12-Item Health Survey Physical and Knee injury and Osteoarthritis Outcome Score Pain scores compared to those in residual valgus. Varus knees showed significantly greater improvement in Knee Society Score Function scores compared to valgus knees. At final follow-up, Knee injury and Osteoarthritis Outcome Score Pain scores were significantly better in varus knees. Patients in varus were 7.79 times more likely to achieve the minimal clinically important difference VR-12 Physical score, while patients in neutral were 3.26 times more likely to achieve the minimal clinically important difference for Knee Society Score Function when compared to valgus knees. Conclusions: Correcting preoperative valgus coronal alignment to neutral or varus yields improved patient-reported outcomes when compared to residual valgus.